Pengaruh Diesel Particulate Filter Tipe Honeycomb Berbahan Tembaga Terhadap Performa Mesin Diesel Empat Langkah (Infotekmesin, 2020)
This study aims to analyze the ability of the copper honeycomb type DPF to the engine performance of diesel engines. The object of research was the 1996 Isuzu Panther engine, which was equipped with one standard exhaust and three experimental exhausts with DPF technology with a variety of mesh sizes 20, 15, and 10 mm. The findings of this study are that the DPF 10 mm is the best variation when compared to the other two variations in terms of increasing engine performance. The reason is that the smaller the mesh, the better the trapping of fine dust particles. Besides, the temperature inside the DPF is also increasing. Also, the use of the right casing design will make the turbulence of the exhaust gas flow lower. Furthermore, the temperature continues to grow, and the little turbulence of the exhaust gas flow will cause self-burning in the DPF. The occurrence of self-burning will have an impact on the complete combustion process, which affects increasing torque and engine power by 2.29-11.68% and 2.94-11.93%, respectively, when compared with standard exhaust.